Penerapan Model Pembelajaran Kooperatif Gallery Walk untuk Meningkatkan Hasil Belajar Bahasa Inggris Siswa - Zaidah, A.P. Harianah (Prosiding Seminar Nasional Fakultas Tarbiyah dan Ilmu Keguruan IAIM Sinjai, 2023)
The goal to be achieved in this study is to find out the application of the Gallery Walk learning model in improving English learning outcomes on the subject of Personal Letter for class XI IPA MAN 3 Bone, Bone Regency. This research is a qualitative descriptive research designed through class room action research. This classroom action research was carried out in two cycles and was carried out in class XI IPA 6 MAN 3 Bone, Bone Regency, for the 2021/2022 academic year, odd semester. The subjects of this study amounted to 31 people. The research instruments were tests and observation sheets. Data were analyzed quantitatively and qualitatively. The results of this study indicate that the Gallery Walk learning model is effectively applied in improving English learning outcomes on the subject of Personal Letter for class XI IPA 6 MAN 3 Bone, Bone Regency. This shows an increase in student scores. In the first cycle, the students' grades and activities were categorized as low with 45.16% completeness which was able to get a score of 70 and above, while in the second cycle, the students' values ​​and activities were categorized as high with 84.85% completeness, which was able to get a score of 75 and above.